Character Education Model and Social Skill Development Through PAI Learning: A Comparative Study of Junior High Schools and Senior High Schools in Bandung - Shabrina, Khalishah Nur; Sumarna, Elan; Islamy, Mohammad Rindu Fajar (Universitas Islam Sultan Agung, 2024)
This research is motivated by the current state of students who show a lack of positive character values. This is indicated by the many brawls, cheating, and lack of responsibility in carrying out learning at school. The PAI learning in the above research is intended to provide a solution to the state of students' character through PAI programs in schools. This research was conducted by comparing learning in 2 schools. So that researchers can compare the success of the programs in the two schools. This research uses a qualitative approach with a comparative method. The findings of this study state that with an innovative and interactive learning model, it can attract students to carry out active learning and teachers can create a conducive classroom atmosphere even though it is not free from the negative impacts that occur. The conclusion of this study is that the PAI learning model related to character education in the 2 schools can have a positive impact on learning.